How Does Dynamic Capability Affect Competitiveness? Environmental Dynamics as a Moderating Variable - Sehabuddin, Ahmad; Widodo, Joko; Murniawaty, Indri; Musthofa, Ubaedul; Budiantoro, Risanda Alirastra; Alrizqi, Damas Gianlugi (Economic Education Analysis Journal, 2023)
This study aims to determine how the influence of dynamic capability variables on entrepreneurial competitiveness is moderated by environmental dynamics variables in the association of young Indonesian entrepreneurs in Semarang City. This research is a type of quantitative research, with a sample in the study totalling 171 respondents. The data analysis technique used in this research is structural equation modelling. The results of this study indicate that adaptive capabilities, absorptive capabilities and innovative capabilities affect entrepreneurial competitiveness. On the other hand, adaptive capabilities and innovative capabilities affect entrepreneurial competitiveness moderated by environmental dynamics, but absorptive capabilities have no effect on entrepreneurial competitiveness moderated by environmental dynamics. The conclusion of this study is that adaptive capabilities, absorptive capabilities and innovative capabilities affect entrepreneurial competitiveness. Environmental dynamics are able to moderate adaptive capabilities and innovative capabilities with competitiveness, but environmental dynamics are not able to moderate the effect of absorptive capabilities with competitiveness.